Frequency of CDH1, CTNNA1 and CTNND1 germline variants in families with diffuse and mixed gastric cancer - Guerra, Joana (2023)
Hereditary diffuse gastric cancer (HDGC) is caused by germline pathogenic variants in the CDH1 and CTNNA1 genes and is characterized by a high prevalence of diffuse gastric cancer and lobular breast cancer. We aimed to evaluate the contribution of CTNNA1 and CTNND1 germline variants to HDGC, as well as to compare the frequencies of CDH1 and CTNNA1 (and eventually CTNND1) germline variants between patients with diffuse and mixed gastric carcinomas. In this study, we report a deleterious CTNNA1 germline variant and four CDH1 pathogenic variants in patients with criteria for genetic testing. None of the cases with mixed gastric cancer carried pathogenic variants in either the CDH1 or the CTNNA1 genes, so there is no evidence to use this tumor type in testing criteria.